PENGARUH DIVERSIFIKASI PRODUK TERHADAP KEPUASAN KONSUMEN KOPI BAKAR BAPAK N’DUT PANDEGLANG: PENGARUH DIVERSIFIKASI PRODUK TERHADAP KEPUASAN KONSUMEN KOPI BAKAR BAPAK N’DUT PANDEGLANG - Marsalino; nurul hudaini, Indah (NIAGARA Scientific Journal, 2025)
The indonesians like to talk about a variety of topics to life update while sipping drinks make coffee shop is always crowded.A convenient atmosphere whom he also music played make drinking coffee so new lifestyle.There are the new companies who often allow work. Coffee fuel artificial sir endut is quite famous among travelers. Because his thick and tasty coffee can treat fatigue.In this coffee shop, coffee lovers dont expect to be able to taste packaged coffee like esspreso, moccachino let alone americano.Why, other than the coffee bar barrel coffee burning menu, The coffee shop provides a traditional coffee menu called cofielamure, I have coffee and a coffee bar..All of them are embroidered manually with a very traditional technique. As for the problem formula in this study: how is the diversification of the product in Kopi Bakar Bapak N’dut Pandeglang? , how can consumer satisfaction in Kopi Bakar Bapak N’dut Pandeglang? , and how much product diversified affects consumer satisfaction in Kopi Bakar Bapak N’dut Pandeglang? According to the results of the responders that the average answer and response to the responses to the statements about the diversification of the 2.85 product, this number shows good criteria., And the average response and response to the response to the statements on consumer satisfaction is 2.81. This number shows good criteria. From calculations obtained results by 86.4 %.This shows that both variables affect each other by 86.4 %.That percentage shows 86.4 % diversified products affect the satisfaction of the customer's On Kopi Bakar Bapak N’dut Pandeglang while the rest of 13.6 % is influenced by other non-scientific factors Keywords : Diversified Products And Customer Satisfaction